Pencegahan Hama Kera Ekor Panjang Sebagai Upaya Mengatasi Permasalahan Petani di Dusun Tekik, Desa Ngloro, Kapanewon Saptosari, Kabupaten Gunungkidul - Sahri, Mustofa Sahri; Salsabila, Aini; Hasanah, Laili Mahfuzhotul; Daulay, Asroito Mafazah; Al Hazza, M. Rofiq Rista; Rahmadani, Kasih (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Agriculture in Tekik Hamlet, Ngloro Village, Gunungkidul Regency has great potential as a major source of income for the community. However, a major challenge faced by farmers is the infestation of long-tailed macaques, which threatens their crop yields and welfare. To address this issue, the author initiated a socialization program on long-tailed macaque pest prevention, which aims to increase farmers' understanding and knowledge of effective methods in dealing with the threat. The program includes stages such as problem identification, target analysis, material preparation, media selection and socialization methods, cooperation with related parties, as well as program implementation and evaluation. The positive impact of the program can be seen in the reduction of losses due to macaque attacks over the 15 days following the socialization. The program also highlighted the importance of collaboration between the academic world, student organizations and the community in addressing challenges in the agricultural sector.